PENCEGAHAN PERCERAIAN PADA PASANGAN PERNIKAHAN DINI DI KECAMATAN PARON KABUPATEN NGAWI (Studi Kasus di Pengadilan Agama Kabupaten Ngawi) - Muhammad Jefri Hidayat; Habibi Al Amin (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
The phenomenon of divorce in early married couples is not something that usually occurs in society, generally the factors that cause divorce among early married couples are economic, but in the Ngawi Religious Court, especially in Beran sub-district, there are several points that are the cause of the divorce, as in the problem formulation which the author has created will explain first what are the factors that cause the divorce of early married couples at the Ngawi Regency Religious Court? secondly, what are the efforts of parents and the efforts of the Ngawi Regency Religious Court to prevent divorce among early married couples? This research uses qualitative field methods, where the data obtained will be reduced using a descriptive method This research concludes that the first factor causing divorce in early married couples is a lack of mental readiness in couples who marry early, the second is economic factors, and the third is the lack of parental education regarding marriage, as for parents' efforts to prevent divorce in couples. The first is to give children time to ask questions about what is going on in their household, the second is to teach couples in early marriage how to earn a living. And the Ngawi Regency Religious Court's efforts to prevent divorce in early marriage couples, firstly rejecting the lawsuits of early marriage couples, secondly providing education to parents to advise children about facing marriage.